THE ROLE OF OYSTER SHELL EXTRACT AS A STIMULANT OF SPERM MOTILITY FOR PATIENTS WITH SECONDARY INFERTILITY (ASTHENOSPERMIA) AND DIABETES (TYPE II) BEFORE AND AFTER IN VITRO PREPARATION FOR IUI (American Journal of Interdisciplinary Research and Development, 2022)
diabetes mellitus diabetes mellitus the most common diseases that present in many infertile patients. This study was conducted to overwhelm the negative response for the diabetes semen by in vitro activation techniques using a medium containing motility stimulants (i.e oyster). The medium used for in vitro activation was Hams F12 with 0.5% (oyster ) and two techniques were performed namely; wash and spin technique and density gradient technique. The results showed that the mean of sperm motility (grade A and grade B ) after activation by using density gradient technique with medium containing 0.5% (oyster) was significantly (P